Sistem Informasi Keuangan Berbasis Web pada Kantor Dinas Perhubungan Kota Medan - Riski Ananda (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
An information system is used to manage and present data so that it benefits an organization. Effective financial management is crucial for government agencies, including the Medan City Transportation Department, to ensure transparency and accuracy in financial records. However, the manual method still used has weaknesses, such as recording errors and reporting delays. Therefore, this study aims to design and develop a web-based financial information system to address these issues.The system features transaction recording, financial reporting, real-time data processing, and more efficient budget management. This study uses the waterfall software development approach, which includes analysis, design, implementation, testing, and maintenance. The results show that this system can improve work efficiency, reduce errors in financial management, and support data-driven decision-making.